DAMPAK EKONOMI, RISIKO, DAN FAKTOR YANG MENYEBABKAN TERJADINYA LONJAKAN PENERBITAN SUKUK KORPORASI DI INDONESIA - Al Ghifary, Muhammad Waqif; Aliffa Rahmadanni (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
The Economic Impact, Risk Profile, and Drivers Behind the Surge in Corporate Sukuk Issuance in Indonesia. The issuance of corporate sukuk in Indonesia has risen sharply over the past five years, reaching Rp160.1 trillion in the third quarter of 2025. This study aims to examine the economic impacts, risk profile, and key factors driving the surge in corporate sukuk issuance. The research adopts a descriptive–qualitative approach using secondary data sourced from OJK reports, the Indonesia Stock Exchange, and publications related to the Islamic finance industry. The findings indicate that the growing volume of sukuk issuance has contributed positively to corporate economic performance, particularly through improved capital structure and reduced funding costs supported by competitive yields. Moreover, the higher issuance activity has stimulated local economic growth, especially by creating new job opportunities and increasing real-sector activities financed through sukuk instruments. However, the rapid rise in sukuk issuance also brings additional risks, including default risk, liquidity challenges due to a relatively shallow secondary market, and uncertainties in macroeconomic conditions. The study identifies several main factors behind this surge: declining policy interest rates, stronger demand for Sharia-compliant financing, regulatory incentives, and investors’ positive perception of sukuk stability. These results highlight the need for stronger corporate governance, better secondary market liquidity, and more harmonized regulations to ensure the sustainable development of Indonesia’s corporate sukuk market